2006
DOI: 10.2114/jpa2.25.29
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Physiological Characteristics and Thermal Sensation under Identical Thermal Conditions

Abstract: Seasonal variations of human thermal characteristics were inspected in thermal comfort and when constantly indoors. Metabolic rate, tympanic temperature, skin temperature, body fat, body weight and thermal sensation were measured under identical thermal conditions in a chamber over the course of one year. Experiments were carried out for each subject in both summer and winter. Six subjects were measured 35 times in summer and 45 times in winter. one subject was measured weekly for 14 months. Measurements for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…The health benefit of the training programme was demonstrated by pronounced increment of MVC and lean body mass in physically inactive men. Because body fat is reportedly lower in summer than in winter [25], the changes in body fat mass in the control group could be explained by seasonal variations. However, since no measurements of erythropoiesis (i.e., reticulocytes), blood/plasma volumes, Hb-mass and blood viscosity were made before and after the training, this makes it difficult to suggest precise mechanisms behind the changes in the observed red blood cell variables.…”
Section: (Fl)mentioning
confidence: 94%
“…The health benefit of the training programme was demonstrated by pronounced increment of MVC and lean body mass in physically inactive men. Because body fat is reportedly lower in summer than in winter [25], the changes in body fat mass in the control group could be explained by seasonal variations. However, since no measurements of erythropoiesis (i.e., reticulocytes), blood/plasma volumes, Hb-mass and blood viscosity were made before and after the training, this makes it difficult to suggest precise mechanisms behind the changes in the observed red blood cell variables.…”
Section: (Fl)mentioning
confidence: 94%
“…The phototropic eVect was due exclusively to their male subjects, probably because they were more involved in seasonal sports. A detailed study of six Japanese subjects (Umemiya 2006) found a larger 15% increase of body fat during the winter months, associated with a 12% decrease in metabolic rate; these changes lagged behind the decrease of environmental temperatures by about 1 month. Ma et al (2006) noted a small but statistically signiWcant seasonal increase of body mass (0.5 kg) among residents of Worcester, Mass; there was an associated increase of body fat, with both peaking during the winter months.…”
Section: Developed Societiesmentioning
confidence: 96%
“…Laboratory experiments [51,52] found that for the same thermal condition, subjects' skin temperature, tympanic temperature, metabolic rate and body fat were higher in winter than they were in summer.…”
Section: Variation Of Thermal Sensation Between Spring and Autumnmentioning
confidence: 99%